2015
DOI: 10.1111/ecc.12302
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus panel guidelines on geriatric assessment in oncology

Abstract: Introduction Despite consensus guidelines on best practice in the care of older patients with cancer, geriatric assessment (GA) has yet to be optimally integrated into the field of oncology in most countries. There is a relative lack of consensus in the published literature as to the best approach to take, and there is a degree of uncertainty as to how integration of geriatric medicine principles might optimally predict patient outcomes. The aim of the current study was to obtain consensus on GA in oncology to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 83 publications
2
65
0
5
Order By: Relevance
“…Because of funding limitations, only U.S. experts were included. A parallel effort included experts outside of the U.S., 44 and future work will examine the similarities and differences between expert opinion in different parts of the world. Although the experts did come to consensus regarding many treatment-related decisions, the recommendations were often vague (e.g., “modify treatment”) which likely reflects the limited data available.…”
Section: Discussionmentioning
confidence: 99%
“…Because of funding limitations, only U.S. experts were included. A parallel effort included experts outside of the U.S., 44 and future work will examine the similarities and differences between expert opinion in different parts of the world. Although the experts did come to consensus regarding many treatment-related decisions, the recommendations were often vague (e.g., “modify treatment”) which likely reflects the limited data available.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that NGT is superior to moderated discussions in focus groups and other more structured techniques, because it regards individual differences, accounts for the strength of conviction, and documents the progress toward achievement of consensus [41]. Moreover, NGT is well-documented [42], easy to learn and apply [43], as well as largely applied in health care and nursing [44]. Nominal grouping is a highly structured technique designed to maximize the individual contribution of each respondent.…”
Section: Methodsmentioning
confidence: 99%
“…Cognition may be assessed using screening instruments such tools as the Mini Mental Status Exam, the Montreal Cognitive Assessment or the Blessed Orientation-Memory-Concentration Test. 22,23 The clinician should assess whether the patient has decision-making capacity 24 and whether a surrogate decision-maker has been identified. 23 In addition, older adults with underlying cognitive impairment may be more vulnerable to delirium 25 , whether when exposed to medications that are potentially inappropriate in older adults 26 or during acute illnesses.…”
Section: Geriatric Assessmentmentioning
confidence: 99%